Teriparatide and Abaloparatide Have a Similar Effect on Bone in Mice - Brent, Mikkel Bo; Stoltenborg, Frederik Eriksen; Brüel, Annemarie; Thomsen, Jesper Skovhus (Frontiers in Endocrinology, 2021)
The parathyroid hormone-related protein analog, abaloparatide (ABL) is the only bone anabolic pharmaceutical approved for treatment of osteoporosis besides teriparatide (PTH (1–34)) and romosozumab. The present study compared the effect of intermittent PTH (1–34) and ABL on bone tissue directly mole-to-mole in female mice. Forty-seven C56BL/6 mice were randomly allocated to the following groups: Baseline (n = 11), Control (Ctrl) (n = 12), PTH (n = 12), and ABL (n = 12). The mice were injected s.c. with PTH (100 µg/kg), ABL (96 µg/kg), or saline (Ctrl) five days a week for three weeks. To assess the effect of PTH and ABL, the hindlimb bones were analyzed with DXA, µCT, mechanical testing, dynamic bone histomorphometry, and histological quantification of bone cells. In addition, serum calcium concentration was determined. PTH and ABL significantly increased femoral areal bone mineral density (aBMD) (borderline significant p = 0.06 for PTH), femoral mid-diaphyseal bone strength, femoral metaphyseal and epiphyseal and vertebral bone volume fraction (BV/TV), connectivity density, volumetric bone mineral density (vBMD), and bone formation rate (BFR/BS) compared to Ctrl. In addition, ABL also significantly increased mid-diaphyseal cortical thickness and bone area compared to Ctrl. Neither PTH nor ABL significantly increased bone strength at the femoral neck. In conclusion, abaloparatide and PTH have similar bone anabolic properties when compared directly mole-to-mole in mice.